1986
DOI: 10.1002/1097-0142(19860115)57:2<407::aid-cncr2820570239>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the uterine cervix

Abstract: Between 1958 and 1969, 251 patients were treated at Radiumhemmet in Stockholm for adenocarcinoma of the uterine cervix. The histologic specimens were reevaluated. In the 211 cases of pure adenocarcinoma, the 5-year survival rate was compared with that in the total of cervical epithelial malignancies. The rate was lower in the adenocarcinoma cases, with respective crude 5-year survival rates of 84%, 50%, and 9% in Stages I, II, and III. Two modes of treatment, irradiation alone or irradiation plus radical surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 14 publications
(2 reference statements)
1
16
0
Order By: Relevance
“…This may be related to limited number of node-positive patients with adenocarcinoma of cervix. In some studies, similarly, a higher incidence of lymph node metastasis and decreased survival in adenocarcinoma compared to squamous cell carcinoma was reported when stage and tumor size were controlled (13,15,25) . In analysis of patients with metastatic lymph nodes, which included 111 with squamous cell carcinoma and 17 with adenocarcinoma, any statistically significant difference was found in survival between two cell types.…”
Section: Discussionmentioning
confidence: 86%
“…This may be related to limited number of node-positive patients with adenocarcinoma of cervix. In some studies, similarly, a higher incidence of lymph node metastasis and decreased survival in adenocarcinoma compared to squamous cell carcinoma was reported when stage and tumor size were controlled (13,15,25) . In analysis of patients with metastatic lymph nodes, which included 111 with squamous cell carcinoma and 17 with adenocarcinoma, any statistically significant difference was found in survival between two cell types.…”
Section: Discussionmentioning
confidence: 86%
“…Investigations comparing the prognosis of cervical AD with SCC came up with varying results, with certain studies reporting AD to have a poorer prognosis compared to SCC (7-11) and others reporting no statistically significant differences between the two (12)(13)(14)(15)(16). Lymph node metastasis is commonly more aggressive in AD compared to SCC and some studies reported a higher incidence of lymph node metastasis and poorer prognosis in AD compared to SCC after controlling for stage and tumor size (22)(23)(24). However, although the rates of lymph node metastasis in our AD group (19%) and SCC group (12.9%) did not differ significantly, AD was significantly associated with a worse prognosis compared to SCC in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published prospective trial, significantly improved recurrence‐free and overall survival rates were noted for stage IB and IIA cervical adenocarcinoma patients who had radical hysterectomy and pelvic lymphadenectomy compared with those who received radiotherapy ( 28 ) . Some observed comparable results with either primary surgery or radiation ( 17 ) , while the others advocated combined treatment ( 29 ) .…”
mentioning
confidence: 99%